Resin composition for powder coating, powder coating, and article having coating film of said powder coating
By using a specific combination of acrylate resins, the coating film smoothness and rust resistance of the powder coating are improved, and the problems of insufficient smoothness and insufficient rust resistance of the existing powder coating film are solved.
Patent Information
- Application Number
- JP2024562316
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-12-15
- Filing Date
- 2023-11-16
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2043-11-16
AI Technical Summary
The coating film of existing powder coatings is not smooth enough and has insufficient rust resistance.
The powder coating combination containing a specific acrylate resin is used, which is composed of units containing acrylate containing a specific epoxy group, units containing an aromatic ring containing a group, and other units that do not contain the above-mentioned units.
High smoothness, good air-drying, weather resistance and rust resistance of the coating film are achieved.
Smart Images

Figure 0007670250000001 
Figure 0007670250000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition for powder coating, a powder coating, and an article having a coating film of the powder coating. [Background technology]
[0002] In recent years, regulations on organic solvents have become stricter due to problems such as air pollution, and environmentally friendly paints have been attracting attention. Among them, powder paints have been in the spotlight as solvent-free paints from the perspective of environmental protection, and acrylic powder paints in particular have been attracting attention for their use in automobile parts such as aluminum wheels, metal exteriors, and home appliances due to their excellent coating film performance such as weather resistance and stain resistance. However, powder paints have the disadvantage of being inferior in smoothness to solvent-based paints.
[0003] In response to this, powder coatings have been proposed that contain an epoxy group-containing acrylic resin obtained by copolymerizing an alkyl (meth)acrylate ester, an epoxy group-containing acrylic monomer, and other copolymerizable vinyl monomers, and a curing agent having a functional group capable of reacting with an epoxy group (see, for example, Patent Documents 1 and 2). However, although the cured coating films obtained from these powder coatings have improved smoothness, they have a problem of insufficient thread rust resistance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2002-69368 A [Patent Document 2] JP 2000-103866 A Summary of the Invention [Problem to be solved by the invention]
[0005] The problem to be solved by the present invention is to provide a resin composition for a powder coating, which is capable of giving a cured coating film excellent in smoothness, curability, weather resistance and filamentous rust resistance, a powder coating, and an article having a coating film of said coating. [Means for solving the problem]
[0006] As a result of intensive research by the present inventors to solve the above problems, they discovered that a cured coating film obtained from a resin composition for powder paint containing a specific acrylic resin whose essential raw materials are an acrylic monomer having a specific epoxy group, a vinyl monomer having an aromatic ring, and other monomers, has excellent smoothness, curability, weather resistance, and thread rust resistance, and thus completed the invention.
[0007] That is, the present invention relates to a resin composition for powder coating containing an acrylic resin (A) whose essential raw materials are an acrylic monomer (a1) having an epoxy group including 3,4-epoxycyclohexylmethyl(meth)acrylate, a vinyl monomer (a2) having an aromatic ring, and an unsaturated monomer (a3) other than the monomers (a1) and (a2), wherein the monomer components which are raw materials for the acrylic resin (A) contain 5 to 40 mass% of 3,4-epoxycyclohexylmethyl(meth)acrylate, 10 to 40 mass% of the monomer (a2), and 20 to 70 mass% of the monomer (a3), and the epoxy equivalent of the acrylic resin (A) is 450 to 1000 g / eq., the powder coating, and an article coated with the coating. Effect of the Invention
[0008] The resin composition for powder coating of the present invention is capable of forming a cured coating film that is excellent in smoothness, curability, weather resistance and thread rust resistance, and can therefore be suitably used in coatings for coating various articles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The resin composition for powder coating of the present invention is a resin composition for powder coating containing an acrylic resin (A) whose essential raw materials are an acrylic monomer (a1) having an epoxy group including 3,4-epoxycyclohexylmethyl(meth)acrylate, a vinyl monomer (a2) having an aromatic ring, and an unsaturated monomer (a3) other than the monomers (a1) and (a2), wherein the monomer components which are raw materials for the acrylic resin (A) contain 5 to 40 mass% of 3,4-epoxycyclohexylmethyl(meth)acrylate, 10 to 40 mass% of the monomer (a2), and 20 to 70 mass% of the monomer (a3), and the epoxy equivalent of the acrylic resin (A) is 450 to 1000 g / eq.
[0010] First, the acrylic resin (A) will be described. The acrylic resin (A) has an epoxy group and is obtained by copolymerizing the monomer (a1), the monomer (a2), and the monomer (a3).
[0011] The monomer (a1) is a monomer having an epoxy group. Since a coating film having excellent filamentary rust resistance can be obtained, it is important that the monomer (a1) contains 3,4-epoxycyclohexylmethyl (meth)acrylate. However, other monomers such as, for example, glycidyl (meth)acrylate, methyl glycidyl (meth)acrylate, (meth)allyl glycidyl ether, and (meth)allyl methyl glycidyl ether can be used in combination.
[0012] In the present invention, "(meth)acrylic acid" refers to either or both of methacrylic acid and acrylic acid, "(meth)acrylate" refers to either or both of methacrylate and acrylate, "(meth)acrylamide" refers to either or both of methacrylamide and acrylamide, and "(meth)acryloyl group" refers to either or both of a methacryloyl group and an acryloyl group.
[0013] The monomer (a2) is a vinyl monomer having an aromatic ring, and examples thereof include styrene, α-methylstyrene, p-methylstyrene, p-methoxystyrene, divinylbenzene, etc., among which styrene is preferred. These monomers (a2) can be used alone or in combination of two or more kinds.
[0014] The monomer (a3) is an unsaturated monomer other than the monomers (a1) and (a2), and examples thereof include (meth)acrylic acid, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, sec-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, 2-ethylhexyl (Meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, behenyl (meth)acrylate, (meth)acrylamide, N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, Nt-butyl (meth)acrylamide, Nt-octyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, (Meth)acrylonitrile, N,N-dimethylaminoethyl (meth)acrylate, 3-(meth)acryloyloxypropyltrimethoxysilane, 3-(meth)acryloyloxypropyltriethoxysilane, 3-(meth)acryloyloxypropylmethyldimethoxysilane, 2-methoxyethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxy-n-butyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, monofunctional unsaturated monomers such as dimethyl-n-butyl (meth)acrylate, 3-hydroxy-n-butyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate, glycerin mono(meth)acrylate, polyethylene glycol mono(meth)acrylate, polypropylene glycol mono(meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxyethyl phthalate, and lactone-modified (meth)acrylates having a hydroxyl group at the end;Ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, hydroxypivalic acid ester neopentyl glycol di(meth)acrylate, bisphenol A-di(meth)acryl Examples of the acrylic monomers include bifunctional unsaturated monomers such as bisphenol A-EO modified di(meth)acrylate, isocyanuric acid EO modified diacrylate, and the like; trifunctional or higher unsaturated monomers such as isocyanuric acid EO modified triacrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane EO modified tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetraacrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol penta(meth)acrylate, and among these, alkyl(meth)acrylates having an alkyl group with 1 to 4 carbon atoms are preferred for the purpose of increasing the glass transition temperature of the cured coating film and improving the filament rust resistance. These acrylic monomers (a3) can be used alone or in combination of two or more kinds.
[0015] The amount of 3,4-epoxycyclohexylmethyl(meth)acrylate used is 5 to 40 mass % in the monomer component that is the raw material of the acrylic resin (A), and is preferably 10 to 30 mass % because this further improves the smoothness and curing properties of the coating film.
[0016] The amount of the monomer (a1) used is preferably 20 to 40% by mass in the monomer components that are the raw materials of the acrylic resin (A) because smoothness and curing properties are further improved.
[0017] The amount of the monomer (a2) used is 10 to 40 mass% in the monomer components that are the raw materials of the acrylic resin (A), and is preferably 10 to 30 mass% because this further improves the smoothness, curing properties, weather resistance, and filamentary rust resistance of the coating film.
[0018] The amount of the monomer (a3) used is 20 to 70 mass% in the monomer components that are the raw materials of the acrylic resin (A), and is preferably 30 to 70 mass% because this further improves the smoothness, curing properties, weather resistance, and filamentary rust resistance of the coating film.
[0019] The epoxy equivalent of the acrylic resin (A) is 450 to 1000 g / eq, and more preferably 480 to 700 g / eq, in order to provide a coating film with excellent smoothness, curability, weather resistance, and filamentary rust resistance.
[0020] The glass transition temperature of the acrylic resin (A) is preferably from 60 to 90°C, more preferably from 60 to 80°C, since this further improves the smoothness, curability, weather resistance and filament rust resistance of the coating film.
[0021] In the present invention, the glass transition temperature is FOX formula: 1 / Tg = W1 / Tg1 + W2 / Tg2 + ... (Tg: glass transition temperature to be determined, W1: weight fraction of component 1, Tg1: glass transition temperature of homopolymer of component 1) The glass transition temperature of the homopolymer of each component is calculated according to the following formula: The glass transition temperature of the homopolymer of each component is calculated according to the values given in the "Adhesive Technology Handbook" published by Nikkan Kogyo Shimbun or the "Polymer Handbook" published by Wiley-Interscience. The glass transition temperature of the homopolymer of 3,4-epoxycyclohexylmethyl methacrylate is 35°C.
[0022] Furthermore, the number average molecular weight of the acrylic resin (A) is preferably 1,000 to 10,000, more preferably 2,000 to 8,000, in order to provide excellent fluidity and resistance to filamentous rust when melted. Here, the number average molecular weight is a value calculated in terms of polystyrene based on gel permeation chromatography (hereinafter abbreviated as "GPC").
[0023] The acrylic resin (A) can be obtained by a known polymerization method using the monomers (a1) to (a3) as raw materials, but a solution radical polymerization method is preferred because it is the simplest.
[0024] The above-mentioned solution radical polymerization method is a method in which each monomer, which is a raw material, is dissolved in a solvent and a polymerization reaction is carried out in the presence of a polymerization initiator. Examples of the solvent that can be used in this case include hydrocarbon solvents such as toluene, xylene, cyclohexane, n-hexane, and octane; alcohol solvents such as methanol, ethanol, isopropanol, n-butanol, isobutanol, and sec-butanol; ether solvents such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and diethylene glycol dimethyl ether; ester solvents such as methyl acetate, ethyl acetate, n-butyl acetate, isobutyl acetate, and amyl acetate; and ketone solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone. These solvents can be used alone or in combination of two or more.
[0025] Examples of the polymerization initiator include ketone peroxide compounds such as cyclohexanone peroxide, 3,3,5-trimethylcyclohexanone peroxide, and methylcyclohexanone peroxide; 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, n-butyl-4,4-bis(tert-butylperoxy)valerate, and 2,2-bis(4,4-ditert-butylperoxy)cyclohexane. peroxyketal compounds such as 2,2-bis(4,4-ditert-amylperoxycyclohexyl)propane, 2,2-bis(4,4-ditert-hexylperoxycyclohexyl)propane, 2,2-bis(4,4-ditert-octylperoxycyclohexyl)propane, and 2,2-bis(4,4-dicumylperoxycyclohexyl)propane; cumene hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, peroxides; dialkyl peroxide compounds such as 1,3-bis(tert-butylperoxy-m-isopropyl)benzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, diisopropylbenzene peroxide, and tert-butylcumyl peroxide; diacyl peroxide compounds such as decanoyl peroxide, lauroyl peroxide, benzoyl peroxide, and 2,4-dichlorobenzoyl peroxide; peroxycarbonate compounds such as bis(tert-butylcyclohexyl)peroxydicarbonate; and peroxyester compounds such as tert-butylperoxy-2-ethylhexanoate, tert-butylperoxybenzoate, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane; and azo compounds such as 2,2'-azobisisobutyronitrile and 1,1'-azobis(cyclohexane-1-carbonitrile).
[0026] The powder coating resin composition of the present invention contains the acrylic resin (A) described above, but it is preferable that it contains a curing agent (B) having a functional group capable of reacting with an epoxy group, since this further improves the coating film properties.
[0027] The curing agent (B) is a curing agent having a functional group capable of reacting with an epoxy group, and examples thereof include polycarboxylic acid compounds such as suberic acid, azelaic acid, 2,4-diethylglutaric acid, sebacic acid, undecanedicarboxylic acid, dodecanedicarboxylic acid, brassylic acid, tetradecanedicarboxylic acid, pentadecanedicarboxylic acid, hexadecanedicarboxylic acid, heptadecanedicarboxylic acid, octadecanedicarboxylic acid, eicosanedicarboxylic acid, 1,3-cyclohexanedicarboxylic acid, and butanetricarboxylic acid, anhydrides of these polycarboxylic acids, and polyhydric phenol compounds. Among these, aliphatic polycarboxylic acid compounds and their anhydrides are preferred, and dodecanedicarboxylic acid is more preferred, since a high-strength coating film can be obtained. In addition, these curing agents (B) can be used alone or in combination of two or more kinds.
[0028] Regarding the blending amounts of the acrylic resin (A) and the curing agent (B) in the resin composition for powder coating of the present invention, since a coating film with high strength can be obtained, the equivalent ratio (A / B) of the equivalent number of epoxy groups in the acrylic resin (A) to the equivalent number of functional groups capable of reacting with epoxy groups in the curing agent (B) is preferably 0.5 to 1.5, more preferably 0.8 to 1.2.
[0029] To the resin composition for powder coating of the present invention, various known and commonly used additives such as organic or inorganic pigments, leveling agents, flow control agents, antifoaming agents, light stabilizers, ultraviolet absorbers, antioxidants, etc. can be added within the range that does not impair the effects of the present invention. A catalyst can also be added for the purpose of promoting the curing reaction during baking.
[0030] In order to improve the filament rust resistance of the coating film, the resin composition for powder coating of the present invention may further contain silica and hydrolyzable silane compounds such as alkoxysilanes and silane coupling agents within the range that does not impair the effects of the present invention. These compounds may be used alone or in combination of two or more kinds.
[0031] Examples of suitable silane coupling agents include glycidylalkoxysilane and aminoalkoxysilane, etc. Among these, glycidyltrialkoxysilane is preferred because it provides a coating film with excellent filamentary rust resistance, and glycidyltrimethoxysilane is more preferred.
[0032] The amount of the silane coupling agent blended in the resin composition for powder coating is preferably 0.01 to 3 mass %, and more preferably 0.01 to 1 mass %, since a coating film excellent in filamentary rust resistance can be obtained.
[0033] The powder coating of the present invention can be prepared by various known and commonly used methods. For example, the acrylic resin (A), the curing agent (B), and, if necessary, various additives such as pigments and surface conditioners are mixed, and then the mixture is melt-kneaded, followed by fine pulverization and classification, in other words, a mechanical pulverization method.
[0034] The powder coating material of the present invention can be applied to exteriors, home appliances, automobile products, motorcycle products, protective fences, and the like, but since it gives a coating film with a high appearance that is excellent in smoothness, curing properties, weather resistance, and thread rust resistance, it is also suitable for application to metal components such as aluminum wheel alloy components.
[0035] The method of applying the powder coating of the present invention includes various known and commonly used methods such as electrostatic powder coating. The method of forming a cured coating film after applying the powder coating of the present invention can be appropriately selected depending on the type of substrate and the purpose, but it is preferable to bake the coating film at a temperature range of 120 to 250°C for 5 to 30 minutes, since this produces a coating film with excellent weather resistance and filiform rust resistance. The coating film thickness is preferably in the range of 50 to 200 μm. EXAMPLES
[0036] The present invention will be described in more detail below with reference to specific examples. The epoxy equivalent and number average molecular weight of the acrylic resin were measured by the following methods.
[0037] [Method for measuring epoxy equivalent] Measured by hydrochloric acid-pyridine method. 25 ml of hydrochloric acid-pyridine solution was added to the resin, and it was dissolved by heating at 130℃ for 1 hour. Then, it was titrated with 0.1N potassium hydroxide alcohol solution using phenolphthalein as an indicator. The epoxy equivalent was calculated from the amount of 0.1N potassium hydroxide alcohol solution consumed.
[0038] [Method for measuring number average molecular weight] Measured by GPC. Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 4 mg / mL in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following monodisperse polystyrene.
[0039] (monodisperse polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation
[0040] (Synthesis Example 1: Synthesis of acrylic resin (A-1)) A reaction vessel equipped with a stirrer, a thermometer, a condenser, and a nitrogen gas inlet was charged with 67 parts by mass of xylene and heated to 135°C under a nitrogen atmosphere. A mixture consisting of 20 parts by mass of styrene (hereinafter abbreviated as "St"), 40 parts by mass of methyl methacrylate (hereinafter abbreviated as "MMA"), 40 parts by mass of 3,4-epoxycyclohexylmethyl methacrylate (hereinafter abbreviated as "ECHMMA"), and 6.0 parts by mass of t-butylperoxy 2-ethylhexanoate was added dropwise to the reaction vessel over a period of 6 hours, and the temperature was maintained for 6 hours after the end of the addition to carry out a polymerization reaction. Thereafter, the solvent was removed under a reduced pressure of 20 mmHg at 160°C to obtain a solid acrylic resin (A-1) having a number average molecular weight of 3,000, a glass transition temperature of 73°C, and an epoxy equivalent of 490 g / eq.
[0041] (Synthesis Example 2: Synthesis of acrylic resin (A-2)) A solid acrylic resin (A-2) having a number average molecular weight of 4,000, a glass transition temperature of 62° C., and an epoxy equivalent of 650 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the composition of the monomers and polymerization initiator was changed to 15 parts by mass of St, 35 parts by mass of MMA, 20 parts by mass of butyl methacrylate (hereinafter, abbreviated as “BMA”), 30 parts by mass of ECHMMA, and 4.0 parts by mass of t-butylperoxy 2-ethylhexanoate.
[0042] (Synthesis Example 3: Synthesis of acrylic resin (A-3)) A solid acrylic resin (A-3) having a number average molecular weight of 2,500, a glass transition temperature of 67° C., and an epoxy equivalent of 580 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the composition of the monomers and polymerization initiator was changed to 30 parts by mass of St, 25 parts by mass of MMA, 15 parts by mass of BMA, 20 parts by mass of ECHMMA, 10 parts by mass of glycidyl methacrylate (hereinafter, abbreviated as “GMA”), and 8.0 parts by mass of t-butylperoxy 2-ethylhexanoate.
[0043] (Synthesis Example 4: Synthesis of acrylic resin (A-4)) A solid acrylic resin (A-4) having a number average molecular weight of 3,000, a glass transition temperature of 65° C., and an epoxy equivalent of 520 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the monomer composition was changed to 10 parts by mass of St, 40 parts by mass of MMA, 20 parts by mass of BMA, 10 parts by mass of ECHMMA, and 20 parts by mass of GMA.
[0044] (Synthesis Example 5: Synthesis of acrylic resin (RA-1)) A solid acrylic resin (RA-1) having a number average molecular weight of 3,000, a glass transition temperature of 66°C, and an epoxy equivalent of 470 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the monomer composition was changed to 15 parts by mass of St, 35 parts by mass of MMA, 20 parts by mass of BMA, and 30 parts by mass of GMA.
[0045] (Synthesis Example 5: Synthesis of acrylic resin (RA-2)) A solid acrylic resin (RA-2) having a number average molecular weight of 3,000, a glass transition temperature of 62°C, and an epoxy equivalent of 390 g / eq was obtained by the same procedure as in Synthesis Example 1, except that the monomer composition was changed to 15 parts by mass of St, 30 parts by mass of MMA, 10 parts by mass of BMA, 30 parts by mass of ECHMMA, and 15 parts by mass of GMA.
[0046] The monomer compositions of the acrylic resins (A-1) to (A-4) and (RA-1) to (RA-2) synthesized in Synthesis Examples 1 to 4 above are shown in Table 1.
[0047] [Table 1]
[0048] (Example 1: Production and evaluation of powder coating (1)) A resin composition containing 85.0 parts by mass of the acrylic resin (A-1) obtained in Synthesis Example 1, 15.0 parts by mass of dodecanedicarboxylic acid (hereinafter abbreviated as "DDDA"), 0.5 parts by mass of benzoin, and 0.3 parts by mass of a leveling agent (ESTRON's "Resiflow LF") was melt-kneaded using a twin-screw kneader (Tsubako Yokohama Sales Co., Ltd.'s "APV Kneader MP-2015 Model"), then finely pulverized and further classified using a 200-mesh wire screen to obtain powder coating (1).
[0049] [Preparation of cured coating film for evaluation] The powder coating material obtained above was electrostatically powder coated onto an untreated aluminum plate (A-1050P) (7 cm x 15 cm) so that the film thickness after baking would be 80 to 120 μm, and then baked at 170°C for 20 minutes to produce a cured coating film for evaluation.
[0050] [Evaluation of smoothness] The cured coating film for evaluation obtained above was judged using standard plates for visually judging the smoothness of powder coating films by PCI (Powder Coating Institute). There are 10 standard plates, ranging from 1 to 10, with the larger the number, the better the smoothness. The smoothness of the prepared cured coating film for evaluation was evaluated by visually judging which standard plate the smoothness of the prepared cured coating film for evaluation corresponded to.
[0051] [Evaluation of hardening] 0.5 g of the powder coating material obtained above was dropped onto a hot plate heated to 160° C., and the time until the tack disappeared (gel time) was measured. Based on the gel time, the curability was evaluated as follows. ○: Gel time is less than 160 seconds △: Gel time is 160 seconds or more and less than 200 seconds ×: Gel time is 200 seconds or more
[0052] [Weather resistance evaluation] The cured coating film obtained above for evaluation was exposed for 1,000 hours using a QUV ultraviolet fluorescent lamp accelerated weathering tester (manufactured by Q-Lab Corporation, controlled wavelength 310 nm, light irradiation: 0.71 W / m2, 60°C; wet: humidity 90% or more, 50°C, light irradiation / wetting cycle = 4 hours / 4 hours), and the specular reflectance (gloss value) (%) of the coating film after exposure was evaluated as the retention rate (gloss retention rate: %) of the specular reflectance (gloss value) of the cured coating film before exposure [(100 x specular reflectance of the coating film after exposure) / (specular reflectance of the cured coating film before exposure)]. The higher the retention rate, the better the weather resistance. The specular reflectance was measured using a Micro Trigloss manufactured by BYK Corporation. 〇: Gloss retention rate 80% or more △: Gloss retention rate is 70% or more but less than 80% ×: Gloss retention rate less than 70%
[0053] [Evaluation of thread rust resistance] The cured coating film obtained above was cut with a cutter knife into two straight lines of 13 cm each so that they reached the base material of the substrate, and the following test was performed using a CASS tester. Test 1 involved spraying saltwater (prepared by dissolving 2.6 g of copper (II) chloride hydrate, 10 cc of glacial acetic acid, and 500 g of ordinary salt in 10 L of ion-exchanged water) for 6 hours under conditions of temperature 50°C, spray volume 1.2-1.8 cc / h, and spray pressure 0.1 MPa, and test 2 involved leaving the film for 96 hours under conditions of temperature 60°C and humidity 85%, for a total of 5 cycles. After the CASS test was completed, the filamentous rust that had developed from the scratches on the coated plate was visually confirmed, and the filamentous rust resistance of the coating film was judged based on the length of the longest filamentous rust that had grown, as follows: ○: The longest length of the rust thread is 2.0 mm or less △: The longest length of the rust thread is more than 2.0 mm and less than 3.0 mm ×: The longest length of the rust thread exceeds 3.0 mm.
[0054] (Examples 2 to 4: Production and evaluation of powder coating materials (2) to (4)) Powder coating materials (2) to (4) were prepared in the same manner as in Example 1, except that the acrylic resin (A-1) used in Example 1 was changed to acrylic resins (A-2) to (A-4), and various physical properties were evaluated.
[0055] (Comparative Examples 1-2: Production and Evaluation of Powder Coatings (R1)-(R2)) Powder coating materials (R1) to (R2) were prepared in the same manner as in Example 1, except that the acrylic resin (A-1) used in Example 1 was changed to acrylic resins (RA-1) to (RA-2), and various physical properties were evaluated.
[0056] Table 2 shows the blend compositions and evaluation results of the powder coating materials (1) to (4) obtained in Examples 1 to 4 and the powder coating materials (R1) to (R2) obtained in Comparative Examples 1 and 2.
[0057] [Table 2]
[0058] It was confirmed that the cured coating films obtained from the resin compositions for powder coatings of the present invention in Examples 1 to 4 were excellent in smoothness, curability, weather resistance, and filamentous rust resistance and weather resistance.
[0059] On the other hand, in Comparative Example 1, which is an example in which 3,4-epoxycyclohexylmethyl(meth)acrylate was not used as the monomer raw material of the acrylic resin, it was confirmed that the filiform rust resistance of the coating film was insufficient.
[0060] In addition, Comparative Example 2 is an example in which the epoxy equivalent of the acrylic resin is below 450 g / eq, and it was confirmed that the filament rust resistance of the coating film was insufficient.
Claims
1. A resin composition for powder coating containing an acrylic resin (A) whose essential raw materials are an acrylic monomer (a1) having an epoxy group including 3,4-epoxycyclohexylmethyl(meth)acrylate, a vinyl monomer (a2) having an aromatic ring, and an unsaturated monomer (a3) other than the monomers (a1) and (a2), wherein the monomer components which are raw materials for the acrylic resin (A) contain 5 to 40 mass% of 3,4-epoxycyclohexylmethyl(meth)acrylate, 10 to 40 mass% of the monomer (a2), and 20 to 70 mass% of the monomer (a3), and the epoxy equivalent of the acrylic resin (A) is 450 to 1000 g / eq.
2. 2. The resin composition for powder coating according to claim 1, further comprising a curing agent (B) having a functional group capable of reacting with an epoxy group.
3. 3. A powder coating obtained from the resin composition for powder coating according to claim 1 or 2.
4. An article having a coating of the powder coating material according to claim 3.
Citation Information
Patent Citations
Preparation of powder coating
JP2000103866A
Thermosetting powder coating composition for aluminum wheel alloy member and aluminum alloy wheel member
JP2002069368A
Epoxy functional acrylic coating powders and powder coatings from the same having improved filiform corrosion resistance
JP2009209341A
Powder coating and aluminum wheel alloy member coated with the powder coating
JP2015054932A